Transforming Growth Factor‐β1 Modulates the Expression of Syndecan‐4 in Cultured Vascular Endothelial Cells in a Biphasic Manner. Issue 8 (10th April 2017) - Hara, Takato; Yoshida, Eiko; Fujiwara, Yasuyuki; Yamamoto, Chika; Kaji, Toshiyuki
ABSTRACT: Proteoglycans are macromolecules that consist of a core protein and one or more glycosaminoglycan side chains. Previously, we reported that transforming growth factor‐β1 (TGF‐β1 ) regulates the synthesis of a large heparan sulfate proteoglycan, perlecan, and a small leucine‐rich dermatan sulfate proteoglycan, biglycan, in vascular endothelial cells depending on cell density. Recently, we found that TGF‐β1 first upregulates and then downregulates the expression of syndecan‐4, a transmembrane heparan sulfate proteoglycan, via the TGF‐β receptor ALK5 in the cells. In order to identify the intracellular signal transduction pathway that mediates this modulation, bovine aortic endothelial cells were cultured and treated with TGF‐β1 . Involvement of the downstream signaling pathways of ALK5—the Smad and MAPK pathways—in syndecan‐4 expression was examined using specific siRNAs and inhibitors. The data indicate that the Smad3–p38 MAPK pathway mediates the early upregulation of syndecan‐4 by TGF‐β1, whereas the late downregulation is mediated by the Smad2/3 pathway. Multiple modulations of proteoglycan synthesis may be involved in the regulation of vascular endothelial cell functions by TGF‐β1 . J. Cell. Biochem. 118: 2009–2017, 2017. © 2016 The Authors. Journal of Cellular Biochemistry Published by Wiley Periodicals, Inc. Abstract : Effects of the MAPK pathway inhibitors PD98059, LY364947, and SB203580 on the expression of syndecan‐4 in vascular endothelial cells.